Pengaruh Penggunaan Video Animasi Pembelajaran dengan Pendekatan Kontekstual terhadap Hasil dan Motivasi belajar Siswa di SD Inpres 19 Kota Sorong - Sapulette, Rosa orpa; Korneles Viktor Ohoiwutun; Yulian Anouw; Disabella Dayera; Christina Bastian (Innovative: Journal Of Social Science Research, 2024)
Students in learning Mathematics often have difficulties. This is due to conventional learning from teachers. Mathematics learning media must be appropriate and interesting for students. The problem to be solved is about the description of interesting animated videos, the influence of the use of animated videos on learning outcomes and student learning motivation. The purpose is that students can be interested in learning mathematics and there is an increase in learning outcomes and student motivation. The results of the study showed that the average pretest and postest scores of students were 40.6 and 81.6 and the paired samples test was 0.000 smaller than the significant level of 0.05. So it can be concluded that there is a significant influence on student learning outcomes and motivation.